5 The fluro project: a review of the approach and understanding of fluid resuscitation in a military tertiary centre from the perspective of care providers in the emergency setting. Issue 3 (18th July 2018) - Lowe, J; Stevenson, L; Wilding, D; McLaughlin, D; West, M
Abstract : Introduction: The term fluid resuscitation (FR) is defined as the use of fluids to restore a state of normovolaemia, or to correct a hypovolaemic state. To establish normovolaeamia via FR, the term 'fluid bolus' is used to describe a prescribed fluid volume. As such, the authors looked to investigate the understanding of this term and to review approaches to fluid resuscitation by those healthcare workers closely associate with critically unwell patients. Methods: A questionnaire was distributed to all clinical staff across Emergency Medicine (EM), Anaesthesia and Theatres (AT), Intensive Care Medicine (ICM) and Acute Medicine (AM). The questionnaire recorded role, area of responsibility, training grade, type, volume and administration time, time to reassessment and parameters to be assessed in relation to a clinical vignette. The results were then compared directly to the NICE Clinical Audit Standards (NCAS) for FR. Results: 153 responses were received from across all working environments. Overall, 52% of respondents gave volumes aligned with NCAS (500 ml). 99% of respondents suggested crystalloid use with 88% giving an appropriate time for administration of less than 15 min. 55% of respondents suggested appropriate review times (0–5 min). 99% of respondents agreed heart rate and blood pressure should be reassessed, but other parameters for monitoring were poorly recognised. Between specialties, EM suggested larger volumes while ICM were more likely to continuously review the patient during a bolus. AM were the only group to administer fluids over 60 min. EM and ICM were more likely to review lactate as a marker for effect. Higher specialist trainees were more likely to give a larger volume when compared to other grades. Discussion: The overall perception of a fluid bolus varies between specialties and training grades. Most responses were aligned to NCAS with notable outliers. This suggests a discrepancy in the understanding of the term fluid bolus. This may also cause issues in fluid administration with multiple patients. It is therefore suggested that further work be undertaken on clarifying the term 'fluid bolus', aiming to minimise uncertainty and increase understanding to prevent adverse effects.